Neonatal morbidity following control of maternal diabetes with human insulin - Senanayake, M. P.; Gunawardene, M. K. S. (Sri Lanka college of pediatricians, 2000)
Objectives To assess the clinical, biochemical and echocardiographic findings of infants born to diabetic mothers given human insulin and to compare the impact of pre-gestational and gestational diabetes. Design Prospective descriptive study. Method Fifty one infants born to diabetic mothers treated with human insulin were studied. 23 had pregestational and 28 had gestational diabetes. Mode of delivery, prematurity, birth weight, asphyxia, plethora, congenital malformations, hypoglycaemia and hyperbilirubinaemia were analysed. The data was also compared with the details of the total birth cohort group of the same unit. Results Caesarian section was performed in 55%. Birth weights of over 3.5 kg were seen in 15.6 % while prematurity was present in 10%. Small-for-dates (14%), large-for dates (4%), symptomatic hypoglycaemia (2%) asymptomatic hypoglycaemia (12%), plethora (2%), hyperbilirubinaemia (12%), congenital malformations (13%) and cardiac septal hypertrophy (8%) were the main morbidity features. Prematurity, low birth weight and cardiomyopathy were significantly higher in pregestational diabetes. Caesarian sections, prematurity, high birth weight and congenital malformations were higher in the study group when compared to the general birth cohort. Conclusions Morbidity in this series was higher than in the general population despite strict control of diabetes with human insulin
Keywords: Maternal diabetes; human insulin; neonatal morbidity